Analysis of Work Experience, Workload, and Physical Work Environment on Employee Work Productivity at PT. Sujin Ray Indonesia - Khairani, Yunira; Yanti, Eli Delvi; Kholik, Kholilul (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee work productivity is a crucial factor in supporting organizational success, particularly in manufacturing companies that require timeliness, work accuracy, and operational efficiency. Work productivity is influenced by various factors, including work experience, workload, and the physical work environment. This study aims to analyze the effect of work experience, workload, and physical work environment on employee work productivity at PT. Sujin Ray Indonesia. This research employed a quantitative approach with an associative research design. The population of this study consisted of all permanent employees of PT. Sujin Ray Indonesia, totaling 42 employees, and a saturated sampling technique was applied, where the entire population was used as the sample. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis. The analysis procedures included validity testing, reliability testing, classical assumption tests, and hypothesis testing using t-tests and F-tests with the assistance of SPSS 25.0 software. The results indicate that work experience, workload, and work environment individually have a positive and significant effect on employee work productivity. Furthermore, the simultaneous test results show that work experience, workload, and work environment jointly have a significant effect on employee work productivity. The coefficient of determination (Adjusted R²) value of 0.860 indicates that 86% of the variation in work productivity can be explained by work experience, workload, and work environment, while the remaining 14% is influenced by other factors not examined in this study. This research is expected to provide practical insights for companies in improving employee productivity through effective human resource management.